Angioimmunoblastic T-Cell Lymphoma Mimicking Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS Syndrome) - Joanna Mangana; Emmanuella Guenova; Katrin Kerl; Mirjana Urosevic-Maiwald; Valerie C. Amann; Cornelia Bayard; Reinhard Dummer; Lars E. French (Karger Publishers, 2017)
Angioimmunoblastic T-cell lymphoma (AITCL) is a rare, aggressive lymphoma which derives from follicular helper T cells, commonly affecting the elderly population. It accounts for 2% of all non-Hodgkin lymphomas, with a reported 5-year overall survival rate of less than 30%. Very often, the clinical picture of AITCL encompasses systemic symptoms such as generalized lymphadenopathy, hepatosplenomegaly, skin rash, anemia, and polyclonal hypergammaglobulinemia. Here we report on the case of a female patient who presented with clinical features resembling drug reaction with eosinophilia and systemic symptoms (DRESS syndrome) prior to the definitive diagnosis of AITCL. The index of suspicion for cutaneous manifestations of lymphoma, and especially AITCL, must be high, particularly in atypical clinical courses of drug eruptions or if skin lesions relapse and are refractory to standard high-dose systemic corticosteroids.